2018
DOI: 10.1007/s12519-018-0159-1
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of maternal vitamin B12 deficiency detected by newborn screening: first results from a study for the evaluation of 26 additional target disorders for the German newborn screening panel

Abstract: Within 13 months, the study "Newborn Screening 2020" identified additional 12 children with treatable conditions while only marginally increasing the recall rate by 0.1%. Maternal vitamin B-deficiency was the most frequent finding. Even more children could benefit from screening for the additional target disorders by extending the NBS panel for Germany and/or other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…In our data, there was a wide, overlapping range of C3 concentrations in both genetic and acquired vitamin B12 deficiency cases, with some of the highest values found in newborns determined to be unaffected. Two recent papers substantiate our finding that C3 is not a specific marker for disorders of propionate metabolism [13,33]. Within our data, there was also significant overlap in the C3/C2 values between IEM and false positive cases, which differed from the findings of other groups, who have suggested that C3/C2 provides better sensitivity and is more frequently high in genetic rather than acquired conditions [33,34].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our data, there was a wide, overlapping range of C3 concentrations in both genetic and acquired vitamin B12 deficiency cases, with some of the highest values found in newborns determined to be unaffected. Two recent papers substantiate our finding that C3 is not a specific marker for disorders of propionate metabolism [13,33]. Within our data, there was also significant overlap in the C3/C2 values between IEM and false positive cases, which differed from the findings of other groups, who have suggested that C3/C2 provides better sensitivity and is more frequently high in genetic rather than acquired conditions [33,34].…”
Section: Discussionsupporting
confidence: 86%
“…The screening algorithm was later modified to include the ratio of propionylcarnitine to acetylcarnitine (C3/C2) as a primary biomarker. In 2013, Wisconsin lowered the cutoff value for C3 from <6.92 µM to <5.0 µM and implemented second-tier testing for methylmalonic acid (MMA) and methylcitric acid (MCA) to maximize the sensitivity and specificity of the screen, as shown by other published studies [ 8 , 9 , 10 , 11 , 12 , 13 ]. It is widely accepted that early ascertainment of MMA, MCA, and total homocysteine levels through second-tier testing aids in classification of the disease and its severity.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal B12 deficiency was also the most common finding in newborn screening results published recently from Germany. 34…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on published data [ 3 , 10 ], we developed a decision algorithm based on C3 and methionine and distinct ratios of these markers to select samples for measurement of tHCy as a second-tier marker ( Figure 1 ). Following a recent publication [ 12 ] and simultaneous with a change of the analytic instrument after 8 months of screening for suspected B12D, we adjusted the selection algorithm towards a higher number of samples selected via low methionine as well as a stronger emphasis on the C3/Met ratio ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the percentiles and absolute values (in µM) for the different cutoff values used for the two observation periods. Of note, referring to a recent publication [ 12 ], in the second period the selection scheme was modified to select more cases via the methionine- and less via the C3-dependent criteria with an emphasis on the C3/Met ratio ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%